(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation. Effective speaking is important in many situations, be it school, work, or social interaction. Effective development of speaking skills requires constant effort. Here we review and explore the opinions of various experts and several experiences on improving and expanding language.